Neuromuscular disease: 2021 update - Margeta, Marta (Free Neuropathology, 2021)
This review highlights ten important advances in the neuromuscular disease field that were first reported in 2020. The overarching topics include (i) advances in understanding of fundamental neuromuscular biology; (ii) new / emerging diseases; (iii) advances in understanding of disease etiology and pathogenesis; (iv) diagnostic advances; and (v) therapeutic advances. Within this broad framework, the individual disease entities that are discussed in more detail include neuromuscular complications of COVID-19, supervillin-deficient myopathy, 19p13.3-linked distal myopathy, vasculitic neuropathy due to eosinophilic granulomatosis with polyangiitis, spinal muscular atrophy, idiopathic inflammatory myopathies, and transthyretin neuropathy/myopathy. In addition, the review highlights several other advances (such as the revised view of the myofibrillar architecture, new insights into molecular and cellular mechanisms of muscle regeneration, and development of new electron microscopy tools) that will likely have a significant impact on the overall neuromuscular disease field going forward.